FSO cooperative all-active and selective relaying schemes with backup RF antennas - Abou-Rjeily, Chadi (2018)
In this paper, we consider the problem of parallel relaying decode-and-forward (DF) cooperative free space optical (FSO) networks with backup radio frequency (RF) links. We analyze and compare the all-active and selective relaying schemes for 2-relay and 3-relay systems where these schemes can be implemented in the absence and presence of channel state information (CSI), respectively. The analysis is carried out in the case of fully connected systems where each relay is connected to all other relays. We compare the performance of both schemes using an exact outage probability analysis for gamma-gamma FSO fading channels and Rician/Rayleigh RF fading channels. We then apply the cut-set method to derive an upper-bound on the asymptotic performance for the sake of quantifying the achievable diversity orders and coding gains.